Scientific production of master's degree in pharmacoepidemiology in Cuba: Descriptive review of thesis works - Cruz-Barrios, María Aída; Furones Mourelle, Juan Antonio (Horizonte Sanitario, 2022)
Objective: To characterize the research carried out in pharmacoepidemiology based on the master's theses in Pharmacoepidemiology of the National School of Public Health, Havana, Cuba.Materials and method: It was done a descriptive study; 124 theses defended in the four editions of the master's degree were analyzed, between 2010 and 2019. The variables were profession and place of residence of authors, line of research of the master's degree that was addressed, type of study, type of Drug Utilization Research (DUR), pharmacological groups that were investigated and whether the results were published in scientific journals. The results were summarized in percentages. Results: Most of the authors were medicine graduates (50.0%) and 53.2% resided in Havana. The researched lines of most addressed were quality of drug prescription (43.5%) and pharmacovigilance, 30.6%. 72 DUR, prescription-indication type prevailed were identified (27.7%). The analysis of antimicrobials (28.5%) and cardiovascular drugs (29.7%) predominated. Only 22.5% of the investigations were published in scientific journals.Conclusions: The topics of the master's thesis are in accordance with the priorities of the Cuban health system to achieve a rational use of medicines; the research reports that result as the final work of the master's degree constitute a reference of the research in that field in Cuba. The participation of other professionals, the design of other types of studies and the publication of the results should be encouraged.Keywords: Pharmacoepidemiology; Research; Cuba